Peningkatan Motivasi dan Hasil Belajar pada Materi Haji dan Umrah dengan Strategi Practice Rehearsal Pairs di Madrasah - Ma'ruf Yuniarno (Jurnal Pendidikan Madrasah, 2019)
This study is purposed to find out how to improve students' motivation and learning outcomes through Practice Rehearsal Pairs (PRP) strategy in the course of Hajj and Umrah. The research was designed as a classroom action research. The subject of this research was VIIIC grade students of MTs Negeri 1 Bantul of academic year 2016-2017. The results of this study indicate a significant increase in learning motivation. The percentage of students' learning motivation in Pre-cycle was 6.25%. At the meeting I of Cycle I, the student motivation was 40.63% and went up to 50.00% at meeting II. At meeting I of Cycle II, student motivation also rose to 53.13% and increased at the second meeting to 71.88%. There were 22% of total students scored above the Minimum Passing Grade (KKM) at Pre-cycle. At the Meeting I of Cycle I, students who scored ​​above the KKM rose to 41%. At the Meeting II of Cycle I, the average of student score rose to 59%. At the Cycle II Meeting I, it increased to 63% and significantly rose to 78% at Meeting II of Cycle II. In short, the implementation of Practice Rehearsal Pairs strategy in Hajj and Umrah course can improve motivation and learning outcomes by modifying certain substances that are the use of attractive media, seating arrangements, and effective classroom management strategies.